PENDIDIKAN BERBASIS GENDER DALAM KELUARGA MASYARAKAT ACEH - Muhammad Zawil Kiram (Jurnal Community, 2020)
Since it was declared as one of the crucial issues in the Sustainable Development Goals agenda by the United Nations, gender equality has entered every country including in Aceh province. This study aims to reveal the parent’s role in giving gender education for children in the family, and to seek the forms of gender education, and the importance of gender education in families. This study was conducted by using the method of descriptive qualitative with data collection techniques through library research and interview. The result showed that in Acehnese families the role of parents in gender education is not found and there is no gender education. Two factors causing the absence of gender education in Acehnese society. Firstly, the lack of parents understanding about gender equality, and secondly, gender issues are considered as western culture and still taboo to discuss.  Gender education in the family is important because children acquire gender stereotypes at an early age, and they learn about gender equality from their family for the first time.